2009
DOI: 10.2114/jpa2.28.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutathione Depletion on Hypoxia-induced Erythropoietin Production in Rats

Abstract: In vitro studies have indicated that reactive oxygen species modifying cellular redox status are involved in hypoxia-induced erythropoietin (EPO) production. However, the effects of redox balance on hypoxia-induced EPO production in vivo are still not fully understood. To investigate the effect of the change in cellular redox status on EPO generation, we determined whether glutathione (GSH) depletion has a significant influence on hypoxia-induced EPO production in rats. For the inhibition of GSH synthesis, DL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Taking together all the studies, the role of ROS and intracellular redox homeostasis on the HIF1-regulation remains controversial. In a recent in vivo study in rats, Ando et al (2009) showed that the signiWcant increase in EPO concentrations after an acute hypoxic stimulus was not modiWed by a pharmacological inhibition of glutathione synthesis. This raises questions about the central role of cellular redox changes in the hypoxia-induced EPO secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Taking together all the studies, the role of ROS and intracellular redox homeostasis on the HIF1-regulation remains controversial. In a recent in vivo study in rats, Ando et al (2009) showed that the signiWcant increase in EPO concentrations after an acute hypoxic stimulus was not modiWed by a pharmacological inhibition of glutathione synthesis. This raises questions about the central role of cellular redox changes in the hypoxia-induced EPO secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The Withanolide A feeding to rats was done for 21 days prior to and during exposure to hypobaric hypoxia for 7 days. Buthionine sulfoximine (4 mM/kg BW) was dissolved in phosphate buffer saline to a volume of 1 ml and administrered intraperitoneally (i.p) [27] . Metyrapone (50 mg/kg BW) was dissolved in the 40% polyethylene glycol (PEG) (w/v) in physiological saline.…”
Section: Methodsmentioning
confidence: 99%
“…Treating chronic renal failure with exogenous reductive glutathione can improve the reduction of red blood cells, reduce the concentration of oxidized glutathione, decrease the ratio of oxidized/reduced glutathione, stabilize the red blood cell membrane, and prolong the life of the red blood cell [22]. Research has shown that the effects of supplemental reductive glutathione on anemia are remarkable than only use erythropoietin [23].…”
Section: Reduced Glutathionementioning
confidence: 99%